(untitled) (Nigerian Journal of Pharmaceutical Research, 2020)
Background: Oil derived from Cocos nucifera Linne (CNL) has been used in formulating creams; however, its use in formulation of microemulsion is not well documented in literature. Objective: Oils obtained from CNL were characterized, used in the formulation of microemulsions and were evaluated for their antimicrobial properties in comparison with Castor oil BP (CO) and commercially available coconut oil (CACO). Methodology: Oil from CNL was extracted by maceration in hot – water and petroleum ether to yield naturally extracted oil (NEO) and chemically extracted oil (CEO) respectively. The NEO and CEO were used in formulating microemulsions containing pre-determined ratios (3:7, 1:1, 9:1) of oil to surfactant mix (Smix) [containing polyethylene glycol: Tween 80® at ratio 2:1] Characterization of NEO, CEO and microemulsions were carried out using elemental constituents, rheology, physico-and phyto-chemical analysis, thermal stability and antimicrobial profiles as parameters. Statistical analysis was done using ANOVA at p<0.05 Results: The NEO and CEO contained antraquinones and terpenoids, but were devoid of lead, copper, zinc, alkaloids, saponins, cardiac glycosides and flavonoids. Viscosity profiles were in the order CO>CEO>CACO>NEO. The microemulsions were in the size range 54.24±0.26-89.08±0.07 µm. Microemulsions of oil:Smix (3:7) were the most stable. Inhibition ranking was Candida sp.D25 (CEO:Smix>CACO: Smix>NEO: Smix>NEO>CO>CEO), Candida sp.D33 (CEO = CO>CACO: Smix=NEO>CEO:Smix=NEO:Smix), Staphylococcus sp.DS2 (NEO>CO>CACO:Smix>NEO: Smix>CEO: Smix=CEO) and Pseudomonas sp.DP8 (NEO:Smix>CO>CACO:Smix>CEO:Smix=NEO > CEO). Conclusion: Oil derived from CNL has good potentials as an excipient in the formulation of microemulsions and the method of oil extraction had a significant effect on the antimicrobial activities and on the microemulsions formulated using the oils.